Network scheduling algorithm based on Stackelberg Game with incentive strategy - WEI Jiao-long; HU Jin; DAI Wen-juan; ZOU Jia-hong (Tongxin xuebao)
First, a Stackelberg Game network model was built. In this model, the existence of Nash equilibrium was analyzed and the team optimal solution of the network was available. Then a network scheduling algorithm based on Stackelberg Game with incentive strategy which can adjust the network from general state to optimal state by dynamic Game and gradual induction was introduced into the network resource management. The team-optimal solution ensures the stability of network in the optimal state. Finally, the simulation results demonstrate the effectiveness of the algorithm.